Self-healing capacity of advanced lime mortars. Issue 3 (2nd July 2016) - De Nardi, C.; Bullo, S.; Cecchi, A.; Ferrara, L.
Abstract: The addition of new additives and materials to traditional lime mortars may engineer their self-healing capacity, i.e. make them able to repair an occurred mechanical damage. The phenomenon of self-healing may take place both at microscopic and macroscopic level and, in case, can be initiated by a dispersed phase that becomes available as a result of a mechanical damage. The idea underlying this work is hence twofold: first, a mortar is created with a part of the lime protected by an impermeable coating surface, able to make it inert during the phases of setting and hardening; the mechanical characteristic of this material are thus compared to those of a standard mortar. In a second stage, when the material is subjected to an external stress, the protective layer of the treated lime granules, should undergo a rupture which will trigger another step of setting and hardening in the material made dormant by the same treatment. The sealing of the cracks induced by the aforementioned applied stress will hence be made possible by the delayed reaction of hydration. The purpose of the work is to establish whether this kind of material can be employed in structural application with reference to its durability.